2018
DOI: 10.3390/ma11081435
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Metal-Dielectric Nano-Aperture Antenna for Surface Enhanced Fluorescence

Abstract: A hybrid metal-dielectric nano-aperture antenna is proposed for surface-enhanced fluorescence applications. The nano-apertures that formed in the composite thin film consist of silicon and gold layers. These were numerically investigated in detail. The hybrid nano-aperture shows a more uniform field distribution within the apertures and a higher antenna quantum yield than pure gold nano-apertures. The spectral features of the hybrid nano-apertures are independent of the aperture size. This shows a high enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Moreover, these hybrid Au/Si disk-shaped nanoresonators on the gold film have been tested as chemical sensors by using solutions of thiophenol, which are small chemical molecules (thickness of a thiophenol monolayer is around 0.6 nm [47]). Besides, this additional layer of silicon has already allowed the improvement of the fluorescence signal enhanced by the surface for biosensing applications and enhanced single-molecule detection [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these hybrid Au/Si disk-shaped nanoresonators on the gold film have been tested as chemical sensors by using solutions of thiophenol, which are small chemical molecules (thickness of a thiophenol monolayer is around 0.6 nm [47]). Besides, this additional layer of silicon has already allowed the improvement of the fluorescence signal enhanced by the surface for biosensing applications and enhanced single-molecule detection [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the hybrid metal-dielectric nanoslot outperform the gold nanoslot in the near-infrared. As put forward by Lu et al 28 , we mainly attributed these differences to the fact that Si absorbs less than Au in the near-infrared, and consequently there is less quenching. Last but not least, we showed that the intensity enhancement produced by these types of structures heavily depends on the incoming beam used to produce it.…”
Section: Introductionmentioning
confidence: 75%
“…Next, we set out to experimentally test the fabricated nanoantennas for three different wavelengths. The aim of these measurements is i) to demonstrate that the hybrid metaldielectric ZMWs proposed by G. Lu et al 28 are a good choice of ZMW for the near-infrared, and ii) to see how its behavior changes for visible wavelengths. For that, we used the same optical set-up used in some of our previous works 27,29 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent times, such couplings have been experimentally realized on various systems such as metal‐integrated semiconductor nanowires, [ 1 ] metal‐coated dielectric structures, [ 2 ] microsphere coupled with metallic particles, [ 3 ] dielectric nanospheres placed near metallic film. [ 4,5 ] These hybrid structures have been utilized, to design single photon devices, [ 6–8 ] optical antenna, [ 9,10 ] to tune the photoluminescence dynamics of emitters [ 11,12 ] and for enhanced spontaneous emission from emitters [ 13–15 ] down to the level of single molecule with minimized ohmic losses. [ 16,17 ]…”
Section: Figurementioning
confidence: 99%